KINETIKA PERTUMBUHAN BEBERAPA MIKROBA PENGHASIL A - AMILASE MENGGUNAKAN MOLASE SEBAGAI SUMBER KARBON - Trismilah Trismilah; Sumaryanto Sumaryanto (Fakultas Farmasi Universitas Pancasila, 2003)
Molasse as a waste product in sugar industry can be used as alternative carbon source in fermentation, which influences the growth of microbes and production process. In this experiment 5% molasses was used as a medium for producing a - amylase using Bacillus subtilis ATCC 6633, Streptomyces fradiae, and Aspergillus niger. The experiment was done in an Erlenmeyer of 125 ml in a shaker incubator with 250 rpm agitation. The temperature was adjusted to 37°C and the initial pH for Bacillus subtilis ATCC 6633: waste pH=8; Streptomyces fradiae: pH=7, and Aspergillus niger : pH=5. The result showed, that the highest growth and enzyme activity were accomplished by Bacillus subtilis ATCC, while specific growth rate (u max)= 0,1501 in 24 hours attained.